AN ANALYSIS OF SUSTAINABLE DESIGN CONCEPT IMPLEMENTATION IN PRODUCT DESIGN FINAL PROJECTS - Yusron Falahi; Dwinita Larasati (Gorga : Jurnal Seni Rupa, 2024)
In support of the Sustainable Development Goals (SDGs), sustainable design has become one of the main focuses in undergraduate design education. Sustainable design refers to a design process that considers environmental, social, and economic impacts throughout the product lifecycle. This study aims to analyze the implementation of sustainable design in the final projects of Product Design students at Telkom University, as a case study from 2021 to 2023. Using qualitative methods and content analysis, 33 final project samples were evaluated using a sustainable design matrix. The analysis results show that although there is a decline in the quality of certain metrics, such as Biodegradable Materials, there is a positive trend in the use of environmentally friendly materials, material recycling, and efficient, multifunctional design. These findings indicate that students are increasingly aware of the importance of integrating sustainability principles into design, not only as an ethical responsibility but also as an innovative strategy. With a focus on sustainable materials and product durability, students demonstrate their commitment to reducing environmental impact and enhancing the quality of sustainable design.